Penerimaan Panelis Terhadap Teh Herbal Dari Kulit Buah Manggis (Garcinia mangostana L.) Dengan Perlakuan Suhu Pengeringan - Lasma Simanjuntak; Noviar Harun; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The processing of mangosteen rind is still less than optimal, so one of processing mangosteen rind is making herbal tea. The purpose of research is drying mangosteen rind with best quality and knowing the acceptance of panelists from herbal tea of mangosteen rind. Research conducted using a Completely Randomized Design (CRD) with 4 treatments and 4 replications. Each treatment is using drying for 3 hours at different temperatures, namely 75°C, 80°C, 85°C and 90°C. Parameters measured were water content, ash content, crude fiber, antioxidants, toxicity and organoleptic. The result showed the drying temperature significantly affect the water content, crude fiber, organoleptic and not significantly to ash content. The best treatment is drying at 85 ° C with a water content value 7.98; 4,129 ash content; crude fiber 7863; antioxidant 3.95 × 10-34; toxicity of 34.67 and 0.92 overall acceptance. Keywords: mangosteen, drying temperature, mangosteen rind, herbal tea